Aprendendo com o outro: os árabes em Floriano, PI. - Procópio, Oscar Siqueira (2007)
The present study deals with the arrival of Arab people at Floriano city in attempt of showing how the process of social and cultural integration of these immigrants in an inner city of Piauí state has happened as well as identifying the main aspects of this influence upon the society through an analysis of the historical, social and economic context. Due to the difficulty of finding registrations about the theme focused – sometimes, due to own lack of these registrations – we have to use as methodological resources some interviews, besides documents, newspapers and pictures that turned out essential elements to a best comprehension of the proposed objective. In this sense, it can be understood that the insertion of the Arabic culture in Floriano city happened in a similar way to that occurred in other Brazilian cities. But, thanks particularly to the presence of the Syrian and Lebanese people in this city, it can be inferred that some aspects of the Arabic influence suffered are different from those occurred in other places, once the immigrants from those countries not only assimilated the regional culture but introduced elements of their own culture, as those relating to food habits and architectural style, only to exemplify. With their natural ability for the commerce they contributed specially to the increase of this activity in Floriano, introducing new commercial practices, including the credit sale modality. Little by little, winning difficulties caused by language and by prejudices, they become respected citizens and assumed public functions, confirming definitely their valuable contribution to the development of Floriano city.